MR-defined fat infiltration of the lumbar paravertebral muscles differs between non-radiographic axial spondyloarthritis and established ankylosing spondylitis - Akgul, Ozgur; Gulkesen, Arif; Akgol, Gurkan; Ozgocmen, Salih (Taylor & Francis Ltd, 2013)
Objective The aim of our study was to compare the magnetic resonance imaging (MRI)-defined cross-sectional area and semi-quantitative grading of fatty degeneration of lumbar paravertebral muscles in patients with non-radiographic axial spondyloarthritis (nr-axSpA) and established ankylosing spondylitis (AS). Methods Cross-sectional area (CSA) of lumbar paravertebral muscles, including the right and left multifidus (MF), erector spina (ES), psoas (PS), vertebral body and muscle: vertebra ratio (MVr), was measured. Fat infiltration of the paravertebral muscles was graded semi-quantitatively. Results The CSA of the MF, ES and PS muscles and the MVr (at the L2, L3, L4 and L5 levels) were quite similar between patients with nr-axSpA (n = 14) and AS (n = 22). However, patients with AS had higher grades of fat infiltration than those with nr-axSpA (Right L4 grading of MF + ES muscles: 1.4 +/- 0.73 vs. 0.51 +/- 0.52, respectively, p = 0.001; left L4 grading: 1.36 +/- 0.65 vs. 0.38 +/- 0.50, respectively, p < 0.0001). This difference remained significant after adjusting for age and symptom duration. The inter-rater reliability was good (intraclass correlation coefficient 0.75 and 0.85). Conclusions This is first study demonstrating that MRI-defined fatty degeneration differs between patients with nr-axSpA and established AS. Semi-quantitative grading is reliable, and fatty degeneration of paravertebral muscles seems to be related to chronicity and spinal functions in patients with nr-axSpA and AS.
Keywords: Ankylosing spondylitis; Paravertebral muscle; Fat infiltration; Magnetic resonance imaging